1970
DOI: 10.1071/ar9700571
|View full text |Cite
|
Sign up to set email alerts
|

Response to salinity in Glycine. VI. Some effects of a range of short-term salt stresses on the growth, nodulation, and nitrogen fixation of Glycine wightii (Formerly Javancia)

Abstract: Well-nodulated plants of Glycine wightii (formerly G. javanica) grown in sand culture were subjected to 14 days of salinity ranging from nil to 148 m-equiv. sodium chloride per litre of nutrient solution, and the response compared with that of similarly treated nitrogen-fertilized plants. The latter showed less tissue injury and a smaller reduction in growth rate at high salinity than the inoculated plants. During salinity treatment the development of new nodules, and nitrogen fixation by the existing nodules,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
20
4

Year Published

1979
1979
2001
2001

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 0 publications
7
20
4
Order By: Relevance
“…The reduction in dry weight was less conspicuous in the cultivar Edkawi, followed by Momotaro and most significant in UC-97, indicating that Edkawi is more tolerant to salinity stress than the other cultivars, while UC-97 is more sensitive. These results are consistent with those obtained by other researchers (Wilson 1970;Hafeez et al 1988;Delgado et al 1994;Cordovillaet al 1996) who demonstrated that the salt treatment reduced plant growth markedly.…”
Section: Resultssupporting
confidence: 83%
“…The reduction in dry weight was less conspicuous in the cultivar Edkawi, followed by Momotaro and most significant in UC-97, indicating that Edkawi is more tolerant to salinity stress than the other cultivars, while UC-97 is more sensitive. These results are consistent with those obtained by other researchers (Wilson 1970;Hafeez et al 1988;Delgado et al 1994;Cordovillaet al 1996) who demonstrated that the salt treatment reduced plant growth markedly.…”
Section: Resultssupporting
confidence: 83%
“…Numerous researchers (Wilson 1970;Singleton and Bohlool 1984;Grattan and Maas 1988;Hafeez et al 1988;Wignarajah 1990;Delgado et al 1994;Cordovilla et al 1996) have reported that salt treatment reduced plant growth markedly even at low levels. However, we observed that the response of A. pseudoalhagi plants to salt was different in a sense that the whole plant dry weight increased approximately by 170% in the 50 mM treatment at 10 DAT (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Plant growth and dry matter accumulation were reduced even by low salinity levels in Phaseolus vulgaris (Abdel-Ghaffar et al 1982), Glycine wightii (Wilson 1970), Glycine max (Grattan and Mass 1988), Vigna radiata (Hafeez et al 1988), and in K faba cv. Alameda, as shown in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…These effects may be mediated through the effect of salt on the host, or through a specific effect on the microsymbiont itself. In many studies, it was reported that the upper limits for salinity tolerance of Rhizobium were higher than those of their host legumes (Wilson 1970;Bhardwaj 1975;Lauter et al 1981;Singleton et al 1982;Kassem et al 1985;Delgado et al 1993).…”
mentioning
confidence: 99%